1997
DOI: 10.1051/jp4:19971124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variations in Stoichiometry on M-Type Hexaferrites

Abstract: Barium hexaferrite particles prepared by sol-gel technique yield best magnetic characteristics if a large barium surplus is used. Therefore, the powder sample has to be etched after the annealing process in order to get samples without intermediate phases. The used temperatures below 900°C and times shorter than 1h cause nanocrystalline hexaferrite particles with a specific saturation magnetization above 700 Acm2/g and a coercivity up to 470 kA/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…The particle size has been reported to influence the magnetic properties of BaM powders. 4,5,13,17,27,28 In our case, the crystallite sizes are far below the critical size (∼1 m) where single domain state can be energetically realized, 29,30 indicating that the powders behave as monodomain particles. For monodomain BaM powders, M s and H c decrease with decreasing crystallite size due to the surface spin canting and thermal fluctuation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The particle size has been reported to influence the magnetic properties of BaM powders. 4,5,13,17,27,28 In our case, the crystallite sizes are far below the critical size (∼1 m) where single domain state can be energetically realized, 29,30 indicating that the powders behave as monodomain particles. For monodomain BaM powders, M s and H c decrease with decreasing crystallite size due to the surface spin canting and thermal fluctuation.…”
Section: Resultsmentioning
confidence: 97%
“…To obtain a single phase BaFe 12 O 19 , a slight barium ferrite surplus is necessary regardless of the specific wet chemical preparation technique as barium hydroxide is partially soluble in water. 6,9,13 An ammonium hydroxide solution was used as the precipitant to obtain the Ba-Fe-hydroxide precursor. After being washed with ethanol and dried, the precursor was calcined at 500°C for 4 h before it was calcined for another 4 h at various temperatures between 600 and 950°C in order to develop the required barium ferrite phase.…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic parameters such as saturation magnetization (M s ), remanence (M r ), squarness ratio (M r /M s ) and coercivity (H c ) were depicted from hysteresis loops and have been shown in Table [2] and Fig.5(a-c). It was found that doping with Sr at x=0.1 improved the magnetization as compared with the parent compound [28][29][30][31][32][33][34][35]. Increasing the concentration of Sr will decrease the magnetization because the secondary phase increases.…”
Section: Resultsmentioning
confidence: 99%
“…No processamento das ferritas BaM pelo método cerâmico tradicional utilizam-se óxidos e carbonatos onde duas ou três etapas ocorrem para a formação da fase hexaferrita, dependendo do uso do carbonato de bário ou óxido de bário, como apresentado nas equações A a C. A segunda etapa é descrita pela formação da fase intermediária monoferrita BaFe 2 O 4 , o qual tende a reagir com as hematitas relação estequiométrica desta reação é de n = 6, onde n = Fe 2 O 3 /BaO é o fator de estequiometria. O interesse em obter a melhora das propriedades magnéticas das ferritas BaM, como por exemplo a coercividade e a magnetização de saturação, levantou a questão sobre o uso de um excesso de bário (n < 6) no processo de produção das ferritas BaM e as conseqüências deste uso [9,[12][13][14]. Surig et al [13] tem mostrado que as melhores propriedades magnéticas das ferritas BaM têm sido obtidas com valores de n entre 5 e 5,5, para diferentes técnicas de processamento.…”
unclassified
“…Foi mostrado que a razão da melhora das propriedades magnéticas produzidas com valores de n entre 5 e 5,5 é a ocorrência de maior grau de ocupação dos sítios octaédricos pelos íons ferro (50% para n = 5,25) na rede cristalina da ferrita BaM [13,14], após a "lavagem" do material resultante, eliminar a fase intermediária monoferrita BaFe 2 O 4 . n = 5,45 (composição central de 84,50% na região de uma fase sólida no diagrama da Fig.…”
unclassified